Culturally Responsive Health Services at Banjang Community Health Center - Rismawati, Novianti; Monalisha, Zahara; Salsabila, Nor Annisa Rizky; Cahya, Nila (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2026)
Background: This study describes health workers’ perceptions, readiness, and experiences in providing culturally diverse-based services at Banjang Community Health Center. Such services are essential for inclusive and equitable healthcare that respects patients’ differences in ethnicity, religion, culture, language, and personal habits. Method: A descriptive quantitative method was used with open-ended questionnaires completed by 21 health workers, including medical staff, midwives, nurses, and administrative personnel. Data were analyzed descriptively by categorizing responses and identifying themes from six main questions. Result: Results indicate that health workers understand the importance of cultural diversity, are prepared to serve patients from various backgrounds, and demonstrate empathy, effective communication, patience, and professionalism. Support from leadership and colleagues strengthens an inclusive work environment, although challenges such as language differences and local customs remain. Conclusion: Recommendations include cross-cultural communication training, facility improvements, dissemination of diversity policies, and regular evaluations.